Evaluation of Risk Culture Implementation at PT XYZ Financing Company - Nico Priyantha Tarigan; Tubagus Muhamad Yusuf Khudri (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This research evaluates the implementation of risk culture at PT XYZ, focusing on the IRM Framework 2012. Despite its significance, PT XYZ's risk culture remains suboptimal, primarily due to low employee risk awareness. This has led to a three-year surge in the Allowance for Doubtful Accounts, potentially impacting profitability. A mixed method study combining surveys and interviews, was conducted to investigate underlying causes. Results reveal an